The Competition Laws of China and Cameroon: A Comparative Analysis of their Legislative Systems - Yongyeh, Ngalim Elizabeth; Yu, Lu Ming; Mohammed, Naumi Kassim (Comparative and International Law Journal of Southern Africa)
This study aims to compare the competition laws of Cameroon and China, with a focus on the legislative system of the anti-monopoly law of the People’s Republic of China (PRC) and the competition law of Cameroon. In this context, the study examines various aspects, such as the similarities of Cameroon and China’s competition legislative systems, by using secondary data analysis (secondary research). Research on China and Cameroon is significant in terms of determining where both countries need to develop and enhance their competition laws, economic trade and diplomatic relations. Cameroon’s competition law has not been amended in the recent past, while the anti-monopoly law of the PRC was amended in 2022.